An Exploration of Edible Palm Weevil Larvae (Akokono) as a Source of Nutrition and Livelihood: Perspectives From Ghanaian Stakeholders. Issue 4 (December 2017) - Laar, Amos; Kotoh, Agnes; Parker, Megan; Milani, Peiman; Tawiah, Charlotte; Soor, Shobhita; Anankware, Jacob P.; Kalra, Nikhila; Manu, Grace; Tandoh, Akua; Zobrist, Stephanie; Engmann, Cyril; et al.
Background: Meeting the nutritive needs of infants and young children is a challenge in Ghana. Alternative animal source foods, including insects, could enhance infant and young child dietary quality while also improving livelihoods. Objective: To investigate the perspectives of Ghanaian stakeholders on the acceptability of the palm weevil larvae ( akokono ) as a food source and the feasibility of micro-farming this local edible insect as a complementary food for infants and young children. Methods: We conducted an ethnographic study in the Brong-Ahafo Region of Ghana. First, 48 caregivers were asked questions about feeding and care practices, including attitudes toward production and consumption of akokono. Then, a selection of previously interviewed respondents joined 1 of 8 focus group discussions to provide further insight on key themes that emerged from earlier interviews. Concurrently, interviews with 25 other key local stakeholders were conducted. Results: Respondents generally had favorable perceptions of akokono as a nutritious food. A small minority would not consume akokono for religious reasons. Key factors positively influencing the acceptability of akokono as a complementary food were familiarity with the consumption of akokono by the primary caregiver and health worker endorsement of akokono. Stakeholders consider the larvae farmable and were open to its domestication. Conclusions: Anticipated barriers to scaling up akokono micro-farming include a need for greater familiarity with and acceptance of the insect as food for infants and young children and creation of a sustainable market. Engagement with stakeholders, including health workers, will facilitate use of akokono as a complementary food.